Är anfall bästa försvar? - En analys av mainstreampartiers ackommoderingseffekt på nischpartiers valresultat - Thysell,Maria; Zander,Emelie (2019)
The study aims to examine the effects on election results for three nische parties’ in Sweden due to mainstream parties accommodating nische parties’ politics, as well as why these effects appear. This is relevant since mainstream parties may accommodate not because it finds it attractive or aversive, but because the mainstream party recognizes a strategy attractive in order to eliminate an opponent. Furthermore, previous research disagree upon the effects. Consequences of approaching nische parties are examined through analyses of mainstream parties’ election manifestos and compared to the election results that a nische party holds. In addition, the results are discussed as well as explained by three determinants; issue-ownership, legitimization along with point of accommodation. The result indicates that accommodation presumably foster nische party success in the case of the Green Party, but only in the long run. In the case of the Feminist Initiative, the results are even less conclusive, although indicative of that accommodation hinder nische party success. In comparison, the success of the Sweden Democrats cannot be explained by accommodative strategies. This implies that accommodation does not have an universal impact on all nische parties. However, be aware that the discipline suffers from disagreement upon definitions and ambiguous results.
Keywords: accommodation; party competition; mainstream parties; nische parties; determinants